Menumbuhkan Kultur Kebhinekaan (Belajar dari Desa Darmaji Kec. Lumbir Kab. Banyumas) - Robertus Suraji (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2018)
The State of Indonesia is built on a common commitment to diversity. The diversity that exists in Indonesia should be grateful for the grace of Almighty God. Such diversity must also be believed to be the will of God Himself. The diversity has been around for hundreds of years. However, lately there is a group of people who reject the diversity. They even wanted to replace Pancasila as the basis of the state. They reject the diversity because it is affected by global ideology and try to impose that ideology as a way of life of the Indonesian nation. This ideology becomes dangerous because many followed by the younger generation. Therefore, aware of these dangers need to go through efforts to re-grow the culture of diversity that has begun to wear off. Learning from the village Lumbir that has lived the love-loving movement of diversity, then it should be the movement to cultivate the culture of diversity is also developed elsewhere.